Analisis Pengaruh Fundamental Makro dan Fundamental Mikro Terhadap Struktur Kepemilikan, Kinerja Keuangan, dan Nilai Perusahaan pada Badan Usaha Milik Negara yang Terdaftar di Bursa Efek Indonesia - Hwihanus, Hwihanus; Ratnawati, Tri; Yuhertiana, Indrawati (Jurnal Bisnis dan Keuangan, 2019)
This study aims to examine and analyze the relationship between the variability of mu- tuality micro fundamental, macro fundamentals of ownership structure, financial performance, and the value of companies in State-Owned Enterprises listed on the Indonesia Stock Exchange. Re- search population at 20 State-Owned Enterprises listed on Indonesia Stock Exchange. This research method uses purposive sampling with 12 companies in 2010–2015. Data analysis of techniques in this study using Partial Least Square consists of Inner model, Outers model and Weight relation. The test results showed that all hypothesis testing was accepted which showed significant effect with 5% level with t-table 1,960 and rejected macro fundamentals to firm value with t-statistic 0,666262 (H5) and micro fundamentals of company value with t-statistic 1,188469 (H6) and ownership structure on the financial performance of the company with t-statistics 0.953625 (H7).